Carnivalization as a Strategy for Deconstructing Dominant Discourse in Leila S. Chudori’s Short Story Collection Malam Terakhir - Asyuro, Aniqo Dhamar; Huffidah, Wafiq Azim; Fibrianty, Ayu; Mufidah, Naila Aisya; Ilmiyah, Ruhiyatul; Shofah, Novia Adibatus (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This article examines the strategy of carnivalization in the short story collection Malam Terakhir by Leila S. Chudori as a means of dismantling dominant discourses. The study employs Mikhail Bakhtin’s theory of carnivalization within the Russian Formalism tradition, using a descriptive qualitative approach. The analysis focuses on carnivalistic elements that construct alternative meanings and challenge established ideologies. The findings reveal that the stories in Malam Terakhir utilize carnivalistic narrative techniques to deliver social critiques targeting power structures in the realms of history, religion, politics, gender stigma, and the family. Thus, these stories function not merely as entertainment, but also as critical discursive spaces that subvert dominant social orders in Indonesian society.